2015
DOI: 10.1039/c4ay02874k
|View full text |Cite
|
Sign up to set email alerts
|

Local linear embedded regression in the quantitative analysis of glucose in near infrared spectra

Abstract: This paper investigates the use of local linear embedded regression in the context of determination of glucose from NIR spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These intensive control methods require multipled aily blood glucose tests to adjust the insulin dosage and other treatments.H owever, currentlyused analysis method of blood glucose is predominantly based upon blood sampling by pricking af inger. This finger prick method is accurate,b ut not disliked because of the pain and inconvenience,p articularly wheni tr equires multiple daily measurements,r esulting in fewer tests and inadequate blood glucose control [7][8][9][10].T he ideal approach should therefore be noninvasive and continuousg lucosem onitoring. Several attempts have been made to find at ruly suitable means for ac ontinuous glucose monitoring of diabetes [11][12][13].S ome researchers report the use of impedance-based detection system or near-infrared and mid-infrared spectroscopy for noninvasive glucosem onitoring [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These intensive control methods require multipled aily blood glucose tests to adjust the insulin dosage and other treatments.H owever, currentlyused analysis method of blood glucose is predominantly based upon blood sampling by pricking af inger. This finger prick method is accurate,b ut not disliked because of the pain and inconvenience,p articularly wheni tr equires multiple daily measurements,r esulting in fewer tests and inadequate blood glucose control [7][8][9][10].T he ideal approach should therefore be noninvasive and continuousg lucosem onitoring. Several attempts have been made to find at ruly suitable means for ac ontinuous glucose monitoring of diabetes [11][12][13].S ome researchers report the use of impedance-based detection system or near-infrared and mid-infrared spectroscopy for noninvasive glucosem onitoring [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…These intensive control methods require multipled aily blood glucose tests to adjust the insulin dosage and other treatments.H owever, currentlyused analysis method of blood glucose is predominantly based upon blood sampling by pricking af inger. This finger prick method is accurate,b ut not disliked because of the pain and inconvenience,p articularly wheni tr equires multiple daily measurements,r esulting in fewer tests and inadequate blood glucose control [7][8][9][10].T he ideal approach should therefore be noninvasive and continuousg lucosem onitoring. Several attempts have been made to find at ruly suitable means for ac ontinuous glucose monitoring of diabetes [11][12][13].S ome researchers report the use of impedance-based detection system or near-infrared and mid-infrared spectroscopy for noninvasive glucosem onitoring [14,15].Recent efforts have led to noninvasive detecting the chemical biomarkers in human fluids,s uch as sweat, tears, urineorsaliva [16][17][18][19].Amongthem,saliva has been considered extremely attractive as au seful noninvasive alternative to blood analysis for monitoring the hormonal, stress and metabolic states of individuals,d ue to its easy collection by individuals with modest instruction and little discomfort of the tests.M ost importantly,s alivah as good correlation with blood concentrations of numerous analytes [20][21][22].S uch correlation reflects the permeation of multiple constituents from bloodt os alivav ia transcellularo rp aracellular paths.M any studies have revealed that there is ap ositive correlation between blood glucose and salivary glucose and the salivary glucose is markedly affected in diabetes mellitus [23][24][25][26].T herefore,s alivary glucose can be utilized as an alternative diagnostic Abstract:S alivao pens ad oor for noninvasive and painless glucose testing sincei tr eflectsc hanges in the body physiology of diabetic individuals as compared to healthy ones.I nt his paper,aunique,d isposable saliva biosensor has been developed for accurate,low cost, and continuous glucosem onitoring.…”
mentioning
confidence: 99%